2021
DOI: 10.1039/d1sc03308e
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalysed liquid-to-solid transitioning of arylazoisoxazole photoswitches

Abstract: Molecular photoswitches play a vital role in the development of responsive materials. These molecular building blocks are particularly attractive when multiple stimuli can be combined to bring about physical changes,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
1
17
0
2
Order By: Relevance
“… Isomerization schemes of pH-controlled photochromism in ABs and AIZs in previous works 25 , 28 32 (A–C) and p -MeO-AB in this work (D). Instead of conventional acids such as HCl and CF 3 COOH, the steady states in C and D were achieved with CF 3 SO 3 H. ‡ = not observed.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“… Isomerization schemes of pH-controlled photochromism in ABs and AIZs in previous works 25 , 28 32 (A–C) and p -MeO-AB in this work (D). Instead of conventional acids such as HCl and CF 3 COOH, the steady states in C and D were achieved with CF 3 SO 3 H. ‡ = not observed.…”
Section: Introductionmentioning
confidence: 53%
“… 25 In recent work of our own, we reported the pH-gated photoisomerization for AIZ-derivatives, where a strong acid was added to para -alkoxy azoisoxazoles to unlock an isomerization pathway via the protonated E - and Z -isomers. 28 This latest work ultimately led us to revisit and update the pH-response of azobenzenes in the current contribution ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 98%
“…[ 25,28 ] Moreover, para‐ n ‐alkoxy‐substituted AIZ undergo a reversible photo‐induced solid‐to‐liquid phase‐transition at room temperature, as demonstrated by the group of Venkatamarani [ 29 ] as well as by us. [ 30,31 ] Our studies on the use of AIZ as reversible adhesives have shown excellent switching behavior with isomer ratios at the photostationary state of above 90%, outstanding reusability by repeated bonding and debonding due to a rapid and fast and fully reversible photo‐induced phase transition from solid E ‐AIZ to liquid Z ‐AIZ. [ 30 ] Moreover, compared to substituted azobenzenes, AIZ can be synthesized easily with excellent yields.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] Moreover, compared to substituted azobenzenes, AIZ can be synthesized easily with excellent yields. [ 29–31 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation